دراسة حماية الحديد من التآكل في البيئة البحرية باستخدام مستخلص نبات الطيون كمانع تآكل نباتي (Latakia University Journal -Basic Sciences Series, 2016)
In this research we studied the corrosion rate changes of iron samples which are not galvanized in the laborators ( laboratorsies of the faculty of science) and in nature (on the beach of the high-institute sea- research in Lattakia)The Inula extracts were choosen as a plant inhibitor to cover the iron samples and protect it . because this plant is well known in the Coastal area, also it,s very cheap and easy to find and has good anti oxidation properties .The best conditions for (Inula-seawater) extract were : (PH=7 , time =24 hours , concent ration = 10%).The studied iron samples were treated with the ( inula-seawater) extract in the same previous conditions and we studied the corrosion rate changes for those samples and the affectivity of the inhibitor for them .The results were compared in each stage with other samples that were not treated . the treatment and after it were as follows:The velocity of the corrosion in the iron samples (before the treatment with the extract) in 120 days:- in the laboratory tanks was 0.78 mg/cm2 .day, but after the treatment was 0.23 mg/cm2.day -in the drizzle area was 0.80 mg/cm2.day, but after the treatment was 0.47 mg/cm2.day -in the waves area was 0.75 mg/cm2.day , but after the treatment was 0.41 mg/cm2.day - in the depth area was 0.79 mg/cm2.day , but after the treatment was 0.21 mg/cm2.day .تم في هذا البحث دراسة تغير معدل سرعة التآكل على عينات حديدية غير مغلفنة مخبرياً (في مخابر كلية العلوم) وميدانيا (على شاطئ البحر في منطقة البحوث البحرية في مدينة اللاذقية) واختيرت مستخلصات نبات الطيون كمانع تآكل من اجل تغطية العينات الحديدية وحمايتها كون هذا النبات موجوداً في البيئة الساحلية ورخيص الثمن ويمكن الحصول عليه بيسر وسهوله إضافة إلى تمتع هذا النبات بخواص مضادات أكسدة جيدةحددت الشروط المثلى لمستخلص(طيون، ماء بحر) إذ كانت (PH=7.1،الزمن=24ساعة، التركيز = 10%) عولجت العينات الحديدية المدروسة بمستخلص (طيون ،ماء بحر) بالشروط المحددة نفسها سابقا ودرس تغير معدل سرعة التآكل لهذه العينات وفعالية المانع لهذه العيناتقورنت نتائج معدل سرعة التآكل في كل مرحلة مع عينات غير معالجة ، وكانت قيم معدل سرعة التآكل قبل المعالجة وبعد كما يأتي : كان معدل سرعة تآكل العينات الحديدية( قبل المعالجة بالمستخلص) خلال 120 يوما كما يأتي :في الاحواض المخبرية مساوية mg/cm2.day 0.78 اما بعد المعالجة فكانت 0.23 mg/cm2.dayفي منطقة الرذاذ مساوية 0.80 mg/cm2.day اما بعد المعالجة فكانت 0.47 mg/cm2.dayفي منطقة الامواج مساوية 0.75mg/cm2.day اما بعد المعالجة فكانت 0.41 mg/cm2.dayفي منطقة العمق مساوية 0.79mg/cm2.day اما بعد المعالجة فكانت 0.21 mg/cm2.day